2004
DOI: 10.1177/1527002503251712
|View full text |Cite
|
Sign up to set email alerts
|

The Performance-Enhancing Drug Game

Abstract: Antidoping work consumes huge economic resources. Formal understanding of economic forces that drive athletes to use drugs is lacking. Consequently, work on this phenomenon may be of interest to the sports community, especially the antidoping community. This study uses simple game theory to analyze simple two-player games representing various situations of sports activity. The basic findings are the existence of Nash equilibria forcing agents to use drugs that are very often of the prisoner’s dilemma type, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 10 publications
6
90
0
4
Order By: Relevance
“…The dependent variables were related but of a different character. The dependent variable in Table 4 measured to what (TABLE 7) SPONSORS SHOULD WITHDRAW FROM SPORTS AT FIRST-TIME DOPING EXPOSURE (TABLE 5) Haugen (2004) and Eber (2006), which both focused on how to reduce the economic incentives to doping. However, the regression analysis that used this suggestion as the dependent variable was unsuccessful in explaining the variance.…”
Section: Regression Analysesmentioning
confidence: 99%
“…The dependent variables were related but of a different character. The dependent variable in Table 4 measured to what (TABLE 7) SPONSORS SHOULD WITHDRAW FROM SPORTS AT FIRST-TIME DOPING EXPOSURE (TABLE 5) Haugen (2004) and Eber (2006), which both focused on how to reduce the economic incentives to doping. However, the regression analysis that used this suggestion as the dependent variable was unsuccessful in explaining the variance.…”
Section: Regression Analysesmentioning
confidence: 99%
“…Although the 438 participants suggested that they would engage in some forms of cheating when it was 439 within the spirit of the sport (e.g., attempts to 'psych' opponents out or illegal 440 tackling) the degree of rationality in terms of decision making about PEDs was 441 interesting (Backhouse et al, 2007) -even if the athletes weren't going to get caught 442 and they were assured their performance would improve, they still reported that they 443 wouldn't take PEDs. Again, this points to the importance of attitudes and morals as a 444 key feature of the decision-making process (Haugen, 2004). 445…”
Section: Successful By Taking Peds (Laure Et Al 2004) 436mentioning
confidence: 99%
“…La théorie des jeux permet de dépasser l'analyse de la décision économique individuelle avec la prise en compte des interactions stratégiques (Berentsen, 2002 ;Haugen, 2004). Le sportif sait qu'il est en compétition avec trois catégories d'athlètes : ceux qui ne se dopent pas ou plus (une minorité), ceux qui se dopent de façon artisanale, imprudente et peu efficace en raison de la modestie du budget disponible, ceux qui se dopent scientifiquement avec des molécules de synthèse indétec-tables et performantes (une majorité de l'élite).…”
Section: La Théorie Des Jeuxunclassified